2016
DOI: 10.1111/ajr.12285
|View full text |Cite
|
Sign up to set email alerts
|

Examining health and well-being outcomes associated with mining activity in rural communities of high-income countries: A systematic review

Abstract: This review highlights the broader health and well-being outcomes associated with mining activity that should be monitored and addressed in addition to environmental health impacts to support co-existence of mining activities and rural communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
(50 reference statements)
0
18
0
2
Order By: Relevance
“…This review did not include related types of coal mining outside of this region that may be relevant to community health exposures as covered in recent systematic reviews by Jenkins et al (2013) of coal mining and cancer and Mactaggart et al (2016) of mining in rural communities in high-income countries. Although perhaps limiting, we felt justified focusing on the potential health effects from MTR mining in the Appalachian Mountains.…”
Section: Limitations Of This Systematic Reviewmentioning
confidence: 99%
“…This review did not include related types of coal mining outside of this region that may be relevant to community health exposures as covered in recent systematic reviews by Jenkins et al (2013) of coal mining and cancer and Mactaggart et al (2016) of mining in rural communities in high-income countries. Although perhaps limiting, we felt justified focusing on the potential health effects from MTR mining in the Appalachian Mountains.…”
Section: Limitations Of This Systematic Reviewmentioning
confidence: 99%
“…These findings suggest that rural-urban differences in adolescent substance use were largely driven by counties with economic dependence on mining and support the argument that there may be environmental and cultural factors unique to the economic typology of rural communities that influence risk behaviors. 20 While we were not able to ascertain what is driving the higher rates of substance use among young adolescents in mining communities, the higher rates of alcohol and tobacco use behaviors among adults in the mining industry 25,27,30 may play a role. Research has demonstrated that adolescent substance is strongly influenced by parental and family substance use behaviors and attitudes toward substance use.…”
Section: Discussionmentioning
confidence: 91%
“…While we were not able to ascertain what is driving the higher rates of substance use among young adolescents in mining communities, the higher rates of alcohol and tobacco use behaviors among adults in the mining industry may play a role. Research has demonstrated that adolescent substance is strongly influenced by parental and family substance use behaviors and attitudes toward substance use .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations